Circumstances excluding lawlessness in Italian criminal law - RUDZIŃSKA, KAROLINA (Prawo Kanoniczne, 2013)
In the Italian criminal law system there are three types of circumstances that do not result in calling the perpetrator to criminal responsibility, i.e. the circumstances of justification (scriminanti), the circumstances of exculpation (scusanti) and the circumstances excluding punishability (cause di giustificazione in senso stretto). The distinction between “justification” and “excuse” derives from the Anglo-American law tradition where it has always had important legal consequences. The article describes the circumstances of justification (scriminanti) stipulated in Italian criminal law.